Effects of Pasture Type on Metabolism, Liver and Kidney Function, Antioxidant Status, and Plant Secondary Compounds in Plasma of Grazing, Jersey Dairy Cattle During Mid-lactation - Ford, Hunter R.; Busato, Sebastiano; Trevisi, Erminio; Muchiri, Ruth N.; van Breemen, Richard B.; Bionaz, Massimo; Ates, Serkan (Frontiers in Animal Science, 2021)
Some pasture species are rich in phytochemicals, able to improve milk yield and quality and to reduce environmental impacts of livestock farming. Phytochemicals interact with different gene networks within the animal like NRF2, but their overall impact on animal health remains to be fully understood. The objective of this study was to identify the effects of pasture legumes and non-leguminous forbs containing high bioactive compounds on metabolism and activity of the liver, antioxidant response, kidney function, and inflammation of dairy cows using a large array of blood parameters associated with metabolism and the innate immune system. For this purpose, twenty-six parameters as well as the concentration of certain bioactive compounds were assessed in blood plasma, collected from Jersey cows grazing either grass, legume or forb-based pastures. In addition, serum collected from all cows was utilized to detect changes in NRF2 activation in bovine mammary cells (MACT) and hepatocytes. Compared to Grass, cows grazed both Forb and Legume pastures had lower β-hydroxybutyric acid and creatinine and larger vitamin E and the ferric reducing ability of the plasma, supporting an improved antioxidative status for these animals. Compared to both Grass and Legume, cows grazing Forb pasture had lower urea and urea to creatinine ratio, and lower creatinine, indicating a better kidney function. Cows grazing Legume pasture had greater hematocrit, bilirubin, cholesterol, albumin, β-carotene, retinol, and thiol groups but lower ceruloplasmin, paraoxonase, and myeloperoxidase than those grazed Grass and Forb pastures, indicating a positive effect of Legume pasture on liver, oxidative stress, and red blood cells. Plasma of cows in the various pastures were enriched with various isoflavonoids, especially the cows grazed on Forb and Legume pastures, which likely contributed to improve the antioxidative status of those cows. However, this effect was likely not due to a higher activation of NRF2. Overall, these results indicate that forb and legume pastures rich in secondary metabolites do not strongly affect metabolism but can improve the status of the liver and the kidney, and improve efficiency of N utilization and antioxidant response, compared to the grass pasture.